Guanidine Organocatalysis - Selig, Philipp (Synthesis, 2013)
An overview of the most commonly used guanidine organocatalysts and their applications in organic synthesis is presented. Privileged structures of open, monocyclic and bicyclic guanidines and guanidinium salts are showcased with prominent examples from the literature. Free guanidines have found widespread use as strong Brønsted base catalysts in asymmetric synthesis. Guanidinium salts are employed as weak Brønsted acids or hydrogen-bond-donor catalysts and chiral counterions. The nucleophilic and Lewis basic properties of guanidines are still rarely exploited, but, as of late, have been gaining increasing recognition.1 Introduction2 Brønsted Base Catalysis3 Hydrogen-Bond-Donor and Brønsted Acid Catalysis4 Lewis Base Catalysis5 Lewis Acid Catalysis6 Conclusion
Keywords: guanidines; catalysis; stereoselective synthesis; nucleophiles; domino reaction